PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN LQ 45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Duma Rahel Situmorang (Jurnal Ilmiah METHONOMI, 2017)
The objective of the study was to analyze the influence of financial performance measured with Return on Asset (ROA), Debt to Equity Ratio (DER), Price Earning Ratio (PER), and Dividend Payout Ratio (DPR) on the value of companies listed in BEI (Indonesia Stock Exchange) in the period of 2012 – 2015. The research used causal research method. The population was 83 LQ 45 companies listed in the Indonesia Stock Exchange in the period of 2008-2011, and 17 of them were used as the samples during four-year observations so that there were 68 observations all of them were used as the samples, taken by using purposive sampling technique. The data were analyzed by using residual test. The result of this study showed that simultaneously the variables of Profitability (ROA), Cash Position (CP) and Investment Decision (PER) had influence on Dividend Policy. Partially, Profitability (ROA), and Cash Position (CP) had significant positive influence on Dividend Policy (DPR). The variables of Debt Policy (DER) is moderating variables to explain influence Profitability (ROA), Cash Position (CP) and Invsetment Decision (PER) on Dividend Policy.